Severe E-Cigarette, or Vaping, Product Use Associated Lung Injury Requiring Venovenous Extracorporeal Membrane Oxygenation. Issue 4 (April 2020) - Aldy, Kim; Cao, Dazhe James; McGetrick, Molly; Willcutts, David; Verbeck, Guido; De Silva, Imesha; Hsu, Stephanie
Abstract : Objectives: To report a severe case of e-cigarette or vaping product use-associated lung injury with complex course requiring venovenous extracorporeal membrane oxygenation. Design: Case report. Setting: PICU in an academic medical center. Patients: A 16-year-old girl presenting with gastrointestinal and respiratory symptoms was admitted to our PICU after having progressive respiratory failure and bilateral pulmonary ground-glass opacities on chest CT. Interventions: Venovenous extracorporeal membrane oxygenation Measurements and Main Results: After extensive infectious workup was unrevealing, she reported a history of vaping e-cigarette containing either nicotine or delta-9-tetrahydrocannabinol oil prior to symptom onset. She was given a presumptive diagnosis of e-cigarette or vaping product use-associated lung injury. The PICU team in consultation with pulmonology and medical toxicology started high-dose IV methylprednisolone 1 mg/kg bid. Despite initial improvements, she continued to require positive pressure ventilation and developed pneumomediastinum with progression to tension pneumothoraces and a persistent air leak. Unable to maintain her oxygenation, she was placed on venovenous extracorporeal membrane oxygenation for a prolonged course and had a tracheostomy placement. The clinical course, severity, and range of interventions in affected patients around the country have varied widely. Respiratory symptoms have been the most severe, but the constellation of symptoms in e-cigarette or vaping product use-associated lung injury include constitutional symptoms (fevers, weight-loss) and gastrointestinal symptoms (nausea, vomiting, diarrhea). In many cases, steroid use led to rapid clinical improvements. However, other cases with severe illness, like our patient, necessitated high-dose IV steroids, intubation, and venovenous extracorporeal membrane oxygenation. The underlying etiology and pathophysiology of e-cigarette or vaping product use-associated lung injury remains unknown. The Centers for Disease Control and Prevention in conjunction with state/local health departments and the Food and Drug Administration is actively investigating the outbreak. Conclusions: Clinicians need to be aware of the current outbreak of e-cigarette or vaping product use-associated lung injury and ask about vaping in patients presenting with gastrointestinal and respiratory symptoms. Treatment options are anecdotal and necessitate a multidisciplinary approach.